Nitrogen fixing trees in Africa: priorities and research agenda in multiuse exploitation of plant resources - Okigbo, Bede. N. (Pesquisa Agropecuaria Brasileira, 2014)
Tropical Africa south of the Sahara consists of isolated areas of shifting cultivation and larger areas of more or less dense forests, bushes and grassland natural fallows. A few years of cultivation on slash and bum cleared land is alternated with varying periods of fallow during which soil fertility is recuperated if these periods are long enough. Legume trees play an important role in restoring soil fertility and are regular components of natural and also planted fallows. Besides many miscellaneous uses some of these trees have high protein and nutritious seeds for human and animal food. Other legume trees produce leaves which can be eaten as vegetables. These features together with agroforestry use for timber and fuelwood make tree legumes an important part of fallows. Research should concentrate on multiple utility of tree legumes and focalize agricultural systems which relay on them as nitrogen source for agriculture.
Keywords: N2 fixation